PENGARUH PENGGUNAAN MULTIMEDIA INTERAKTIF TERHADAP MOTIVASI DAN HASIL BELAJAR IPA SISWA KELAS VII SMP NEGERI 10 YOGYAKARTA - Zudi Aziz; Nyoman Erosa; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
This study aims to determine the effect of the use of interactive multimedia on motivation and students’ science learning result. The method used in this study is a quasi-experimental method. The research was conducted in SMP Negeri 10 Yogyakarta involving 68 Seventh Grade students are divided into two groups, namely the class VII D as an experimental group and a control group VIIE class. Research results obtained t value (tvalue) students' motivation is greater than the value ttable 1% (3.321> 2,625) means that there are very significant differences in motivation between the experimental class and the control class. From post test data study results demonstrate the value of t (tvalue) is greater than the value ttable 5% (2.520> 1.996) means that there are significant differences in learning outcomes between the experimental class and the control class. It can be concluded that more effective use of interactive multimedia used in science teaching.